Relation between long-term variation of summer-time waves and reanalyzed meteorological characteristics at the northern-pacific coastline of Japan - Nguyen, Trinh Chung (2021)
In this analysis, long-term trends of significant waves in summer-time in duration 1973- 2013 at two northern-Pacific coastline wave stations (Tomakomai and Hachinohe) in Japan are investigated. Then, some related reanalysed meteorological factors which have been retrieved from ERA-20C are analysed to reveal possible relations with the observed waves. The Mann-Kendall tests for monthly mean of wave period indicate long-term increasing trends at 1% significant level in June at both sites. The Lepage tests for monthly mean wave period with sample size of 10 years also detect abrupt jumps at 1% significant level in June around 1988 and 1989 at Tomakomai and Hachinohe, respectively. Averaged values of several related reanalysed meteorological factors in June of study duration around area express light impacts on the increasing trends of wave period at these sites. The average mean of 10 m above sea level wind speed and sea-surface temperature noticeably increase, while the values of sea level pressure slightly decrease at these both sites in this duration.